Intravenous epoprostenol therapy in the treatment of pulmonary arterial hypertension: the Singapore experience. (4th February 2022) - Choo, J; Yap, J; Ismail, AIDILA; Lim, C L; Sumathy, P; Ruan, W; Sewa, D W; Phua, G C; Hong, C; Low, A H L; Lim, S T; Tan, J L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary arterial hypertension (PAH) is a progressive disease with significant morbidity and mortality. While intravenous (IV) Epoprostenol, a prostacyclin analogue, has been shown to improve exercise tolerance, symptoms, hemodynamics and survival, there are challenges with initiation and maintenance of this IV therapy. Purpose: We aim to describe our local experience of the use of IV Epoprostenol in the treatment of PAH patients in Singapore, highlighting various issues and challenges. Methods: From 2016, patients at a tertiary cardiac institution diagnosed with Group 1 PAH and remaining in intermediate to high risk class with progressive symptoms (despite being on maximum tolerable doses of PhosphoDiEsterase-5 inhibitors and Endothelin-1 receptor antagonists) were assessed and counselled for initiation of Epoprostenol therapy. With a fixed set of local protocols, comprehensive assessment and support of a multi-disciplinary team including physicians, specialist nurses and pharmacists, suitable patients were started on this treatment. Results: A total of 12 patients (11 female, mean age 42.8 +/- 11.0 years) were included. The average New York Heart Association class of the patients initiated on Epoprostenol was II-III. The pulmonary artery pressures and pulmonary vascular resistance on right heart catheterization prior to initiation was 52.5 (IQR 47.0-54.0) mmHg and 12.6 (IQR 10.0-14.2) Woods respectively. The duration from diagnosis to time of initiating Epoprostenol was 89 (IQR 62-140) months. Epoprostenol was generally well tolerated. The most common side effect experienced was diarrhea (5/12 patients) followed by headache and musculoskeletal complains (3/12 patients each). Of the 12 patients, 6 passed away after 12 (IQR 10-16) months of Epoprostenol therapy. Of the remaining 6, PAH was diagnosed 110 (IQR 104-136) months ago and Epoprostenol therapy has been continued for 17 (IQR 14-27) months. Of those who survived, right ventricle size and PA pressures on echocardiography remained relatively stable as compared to those who passed on. 2 patients had line related infections requiring a line change 1 and 2 times respectively. Conclusion: While not without its challenges, the establishment of concrete protocols with the support of a multidisciplinary team allows for the introduction of IV Epoprostenol as an additional potential line of effective therapy for PAH patients in Singapore.